Convexity, monotonicity, and positivity results for sequential fractional nabla difference operators with discrete exponential kernels. (20th February 2021) - Goodrich, Christopher S.; Jonnalagadda, Jagan M.; Lyons, Benjamin
Abstract : We consider positivity, monotonicity, and convexity results for discrete fractional operators with exponential kernels. Our results cover both the sequential and nonsequential cases, and we demonstrate both similarities and dissimilarities between the exponential kernel case and fractional differences with other types of kernels. This shows that the qualitative information gleaned in the exponential kernel case is not precisely the same as in other cases.